Enhancing Tomato Cultivation In Qatar Using Date Palm Biochar Associated With Sustainable Agriculture Technology - Hamad Al-Shamari (23752920) (2026)
Sustainable Qatari agriculture SQF is considered one of the ecological farming methods developed by the Agricultural Research Management of the Ministry of Municipality in Qatar to suit the country weather and environmental conditions, under the protected agriculture system in insect-proof net houses. Qatari arid climate and poor soil quality pose significant challenges for sustainable agriculture, particularly in tomato cultivation, a staple crop in the region. This study investigates the potential of date palm biochar, a byproduct of Qatari abundant date palm industry, as a natural soil amendment to enhance tomato production. Date palm waste was pyrolyzed at 500°C to produce biochar, which was then applied with different rates. Tomato plants (Solanum lycopersicum L.), were grown under drip irrigation for two seasons. Results showed that biochar application significantly improved soil physical properties, increasing water holding capacity by up to 30% and reducing bulk density by 15% at the highest application rate. Soil chemical properties also improved, with increases in organic matter (45%), cation exchange capacity (25%), and available nutrients (N: 40%, P: 35%, K: 50%). Tomato plants in biochar-treated soils exhibited enhanced growth, with 20% taller plants and 25% larger leaf areas. Fruit yield increased by 18%, 27%, and 35% in the 2.5, 5, and 10 tons/ha treatments, respectively, compared to control. Additionally, fruit quality improved, with higher lycopene content (30%) and total soluble solids (15%). This study demonstrates that date palm biochar, a locally abundant and renewable resource, can significantly improve Qatari sandy soils, promoting sustainable, natural tomato cultivation. Its adoption could enhance food security, reduce waste, and support Qatari self-sufficiency goals. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx